<nobr id="r1bpv"><listing id="r1bpv"><menuitem id="r1bpv"></menuitem></listing></nobr>
<pre id="r1bpv"></pre>
      <address id="r1bpv"></address>

      <em id="r1bpv"><sub id="r1bpv"><video id="r1bpv"></video></sub></em> <em id="r1bpv"><address id="r1bpv"></address></em>
        <th id="r1bpv"><noframes id="r1bpv">

          <meter id="r1bpv"></meter>
            Paul's Online Notes
            Paul's Online Notes
            Home / Calculus II / Series & Sequences / Binomial Series
            Show Mobile Notice Show All Notes Hide All Notes
            Mobile Notice
            You appear to be on a device with a "narrow" screen width (i.e. you are probably on a mobile phone). Due to the nature of the mathematics on this site it is best views in landscape mode. If your device is not in landscape mode many of the equations will run off the side of your device (should be able to scroll to see them) and some of the menu items will be cut off due to the narrow screen width.

            Section 4-18 : Binomial Series

            In this final section of this chapter we are going to look at another series representation for a function. Before we do this let’s first recall the following theorem.

            Binomial Theorem

            If \(n\) is any positive integer then,

            \[\begin{align*}{\left( {a + b} \right)^n} & = \sum\limits_{i = 0}^n {n \choose i} {a^{n - i}}\,{b^i} \,\\ & = {a^n} + n{a^{n - 1}}b + \frac{{n\left( {n - 1} \right)}}{{2!}}{a^{n - 2}}{b^2} + \cdots + na{b^{n - 1}} + {b^n}\end{align*}\]

            where,

            \[\begin{align*}{n \choose i} & = \frac{{n\left( {n - 1} \right)\left( {n - 2} \right) \cdots \left( {n - i + 1} \right)}}{{i!}}\hspace{0.25in}i = 1,2,3, \ldots n\\ {n \choose 0} & = 1\end{align*}\]

            This is useful for expanding \({\left( {a + b} \right)^n}\) for large \(n\) when straight forward multiplication wouldn’t be easy to do. Let’s take a quick look at an example.

            Example 1 Use the Binomial Theorem to expand \({\left( {2x - 3} \right)^4}\)
            Show Solution

            There really isn’t much to do other than plugging into the theorem.

            \[\begin{align*}{\left( {2x - 3} \right)^4} & = \sum\limits_{i = 0}^4 { {4 \choose i} \,{{\left( {2x} \right)}^{4 - i}}\,{{\left( { - 3} \right)}^i}} \\ & = {4 \choose 0}{\left( {2x} \right)^4} + {4 \choose 1}{\left( {2x} \right)^3}\left( { - 3} \right) + {4 \choose 2}{\left( {2x} \right)^2}{\left( { - 3} \right)^2} + {4 \choose 3}\left( {2x} \right){\left( { - 3} \right)^3} + {4 \choose 4}{\left( { - 3} \right)^4}\\ & = {\left( {2x} \right)^4} + 4{\left( {2x} \right)^3}\left( { - 3} \right) + \frac{{4\left( 3 \right)}}{2}{\left( {2x} \right)^2}{\left( { - 3} \right)^2} + 4\left( {2x} \right){\left( { - 3} \right)^3} + {\left( { - 3} \right)^4}\\ & = 16{x^4} - 96{x^3} + 216{x^2} - 216x + 81\end{align*}\]

            Now, the Binomial Theorem required that \(n\) be a positive integer. There is an extension to this however that allows for any number at all.

            Binomial Series

            If \(k\) is any number and \(\left| x \right| < 1\) then,

            \[\begin{align*}{\left( {1 + x} \right)^k} & = \sum\limits_{n = 0}^\infty { {k \choose n} {x^n}} \,\\ & = 1 + kx + \frac{{k\left( {k - 1} \right)}}{{2!}}{x^2} + \frac{{k\left( {k - 1} \right)\left( {k - 2} \right)}}{{3!}}{x^3} + \cdots \end{align*}\]

            where,

            \[\begin{align*}{k \choose n} & = \frac{{k\left( {k - 1} \right)\left( {k - 2} \right) \cdots \left( {k - n + 1} \right)}}{{n!}}\hspace{0.25in}n = 1,2,3, \ldots \\ {k \choose 0} & = 1\end{align*}\]

            So, similar to the binomial theorem except that it’s an infinite series and we must have \(\left| x \right| < 1\) in order to get convergence.

            Let’s check out an example of this.

            Example 2 Write down the first four terms in the binomial series for \(\sqrt {9 - x} \)
            Show Solution

            So, in this case \(k = \frac{1}{2}\) and we’ll need to rewrite the term a little to put it into the form required.

            \[\sqrt {9 - x} = 3{\left( {1 - \frac{x}{9}} \right)^{\frac{1}{2}}} = 3{\left( {1 + \left( { - \frac{x}{9}} \right)} \right)^{\frac{1}{2}}}\]

            The first four terms in the binomial series is then,

            \[\begin{align*}\sqrt {9 - x} & = 3{\left( {1 + \left( { - \frac{x}{9}} \right)} \right)^{\frac{1}{2}}}\\ & = 3\sum\limits_{n = 0}^\infty { {\frac{1}{2} \choose n} {{\left( { - \frac{x}{9}} \right)}^n}} \,\\ & = 3\left[ {1 + \left( {\frac{1}{2}} \right)\left( { - \frac{x}{9}} \right) + \frac{{\frac{1}{2}\left( { - \frac{1}{2}} \right)}}{2}{{\left( { - \frac{x}{9}} \right)}^2} + \frac{{\frac{1}{2}\left( { - \frac{1}{2}} \right)\left( { - \frac{3}{2}} \right)}}{6}{{\left( { - \frac{x}{9}} \right)}^3} + \cdots } \right]\\ & = 3 - \frac{x}{6} - \frac{{{x^2}}}{{216}} - \frac{{{x^3}}}{{3888}} - \cdots \end{align*}\]
            天天干夜夜爱 天天色播 天天射天天舔 <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <文本链> <文本链> <文本链> <文本链> <文本链> <文本链>